2018
DOI: 10.32693/bomg.33.2.2018.571
|View full text |Cite
|
Sign up to set email alerts
|

Foraminiferal Analysis Related to Paleoceanographic Changes of Arafura Sea and Surrounding During Holocene

Abstract: Arafura Sea is located between Papua and Australia as a part of Sahul Shelf. It is strongly influenced by ITF, ITCZ replacement, monsoon, and ENSO circulation that interplay with local mechanism. To understand the paleoceanographic parameter changes during Holocene, we conducted foraminiferal quantitative analysis from a 152 cm length sediment core (Aru–07), in every 10 cm interval. This sediment core was retrieved from 134o00’33.6” E, 5o55’51.59” S, by RV Geomarin 3 belongs to Marine Geological Institute. Geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…However, high stratification in deep water basins was also identified as anoxic when circulation is restricted. In 1988, east Indonesian basins with deep characteristics showed no anoxic conditions (Van Aken et al 1988); however, recent studies have indicated their development develop into low oxygen basins (Muripto 2016;Gustiantini et al 2018). In another SEA area, Bengal Bay is a naturally productive area that is indicated by upwelling activities.…”
Section: Unique Features Of Oxygen Dynamics In Southeast Asiamentioning
confidence: 99%
“…However, high stratification in deep water basins was also identified as anoxic when circulation is restricted. In 1988, east Indonesian basins with deep characteristics showed no anoxic conditions (Van Aken et al 1988); however, recent studies have indicated their development develop into low oxygen basins (Muripto 2016;Gustiantini et al 2018). In another SEA area, Bengal Bay is a naturally productive area that is indicated by upwelling activities.…”
Section: Unique Features Of Oxygen Dynamics In Southeast Asiamentioning
confidence: 99%